Pemanfaatan Teknologi Pada Media Pembelajaran Berbasis Etnomatematika - Lu'luilmaknun, Ulfa; Novitasari, Dwi (Mandalika Mathematics and Educations Journal, 2024)
By using technology, learners can better understand mathematical concepts that are relevant to their local culture. Ethnomathematics focuses on the application of mathematics in a cultural context, and educational technology allows for the creation of more interactive and contextual learning media. The purpose of this study is to review articles related to the use of technology in ethnomathematics-based learning media. The Systematic Literature Review (SLR) method was used in this study to review existing literature on the use of technology in ethnomathematics-based learning. There were 14 relevant articles in 2024 selected and analyzed using SLR to determine the opportunities for technology in creating learning media based on local culture. The results of the analysis show that technology and culture have been utilized in mathematics learning and have positive effects. However, to achieve optimal success, special attention needs to be paid to aspects of technology accessibility and the development of materials that are relevant based on local culture